Self Directed Learning Model on Social Sciences Learning Outcomes in Grade IV Students of Elementary School - Iin Rohkmawati Ibrahim; Samuel P Ritiauw; Leonid Ritiauw (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The low learning outcomes of students in social sciences, especially in the material of cultural traditions in Indonesia, are often caused using learning models that do not encourage students' independence in exploring the material. This study aims to examine the effect of the self-directed learning model on the learning outcomes of fourth-grade students at Elementary School 2 Latihan SPG Ambon in the social studies subject of cultural traditions in Indonesia. Method: This study uses a quantitative approach with an experimental method. Data collection techniques include written tests, observation, and documentation. Data analysis is carried out through instrument validity and reliability tests, as well as prerequisite tests that include normality and homogeneity tests. Hypothesis testing is conducted to ascertain the significant impact among variables. The results of the study indicate that the self-directed learning model has a significant effect on improving student learning outcomes. This improvement is evidenced by the rejection of H0 and acceptance of Ha through the acquisition of a significance value of 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05). Descriptive analysis strengthens the finding that the application of this model effectively encourages better academic achievement. This research contributes to teachers' selection of innovative, student-centered learning models to improve the quality of social studies instruction in elementary schools. Furthermore, these results serve as a reference for schools in their efforts to increase the effectiveness of their independent learning-based curriculum.